Human Amylin as a Novel Diagnostic Marker for Hypothyroidism in Iraqi Patients - Duha Khalil Ibrahim; layla othman (مجلة بغداد للعلوم)
Amylin is a peptide hormone that the pancreas cell secretes along with insulin.  As a neuroendocrine hormone that sends a specific signal to the brain, amylin is essential for maintaining homeostasis in the metabolism. The goal of the current study is to determine the role of Amylin as a diagnostic   marker of hypothyroidism.  The 120 samples were divided into two groups (80 patients with hypothyroidism) and the second group (40 healthy people). Amylin levels significantly increased compared to the control group in the group with hypothyroidism, according to the data (p < 0.001). Amylin levels raised in Iraqi patients with Hypothyroidism. Amylin a good diagnostic marker for Hypothyroidism with most accurately, sensitively cut off value 51.